Panic Buying In The Era of Covid-19 Pandemic: Consumer Behavior Perspective of Monzer Khaf - Fita Nurotul Faizah; Ani Nur Khabibah; Siti Afidah (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
Covid-19 has a diverse impact on various sectors of human life and causes several phenomena, one of which is the phenomenon of panic buying. Concern over the closure of a number of public facilities resulted in the price of masks, hand sanitizers, tissues, soap and other basic necessities, experiencing scarcity due to excessive demand. That resulted in an increase in prices on several items on the market. Of course, consumer behavior is very contrary to Islam, because it can damage the economic order in society. The purpose of this study is to review panic buying in the pvidemic era 19th in the perspective of consumer behavior according to Monzer Khaf. The analytical method used in this research is the study of literature. The data used in the study are secondary data that are reviewed from existing studies and some other literature. In the first part of this study reviewing panic buying, the second part will review the impact of panic buying, the third research will review the consumption theory of Monzer Khaf and the last analysis of the relationship of the phenomenon of panic buying with the consumption theory of Mozer Khaf.